1981
DOI: 10.1016/s0022-5347(17)54746-1
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Myelolipoma Simulating a Retroperitoneal Malignant Neoplasm

Abstract: We describe a case of a large myelolipoma (15 by 12 cm. maximum diameter) that was removed surgically and resembled clinically and semeiologically a malignant retroperitoneal tumor. The patient also had chronic pancreatitis and cholelithiasis. Experimental findings, as well as the frequent association of myelolipomas (usually small) with several chronic diseases, suggests that the adrenal myelolipoma is not a true neoplasm but, rather, a choristoma or, perhaps even more likely, a hyperplastic and/or metaplasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The myelolipoma can be present concurrently in many diseases, such as arteriosclerosis, hypertension, osteomyelitis, pyelonephritits, peptic ulcer, diabetes mellitus, other tumors and various endocrine disorders [1,4,10,11,14], In addition to myelolipoma our patient had acantho sis nigricans and a hyperandrogenic state, an association not previously reported.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The myelolipoma can be present concurrently in many diseases, such as arteriosclerosis, hypertension, osteomyelitis, pyelonephritits, peptic ulcer, diabetes mellitus, other tumors and various endocrine disorders [1,4,10,11,14], In addition to myelolipoma our patient had acantho sis nigricans and a hyperandrogenic state, an association not previously reported.…”
Section: Discussionmentioning
confidence: 59%
“…Recently, improved diagnos tic techniques permit the discovery of both asymptom atic and symptomatic myelolipoma lesions in living pa tients [1][2][3][4], Myelolipoma is generally single, rarely reaches large size, with no sex predominance, specific age or hormone activity. Occasionally it is symptomatic and may cause pain, hematuria, hypertension [4][5][6], nephrotic syn drome by compression of the ureter and renal vein [7], and retroperitoneal hemorrhage [6,8].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature many of these patients are male, hypertensive and newly discovered diabetics as was in our case 3,5 . Case reports indicate that some of the larger myelolipomas have been misinterpreted as retroperitoneal liposarcomas on radiological examinations 18 . Giant adrenal myelolipomas are usually treated by simple adrenalectomy and are completely curable 17 …”
Section: Discussionmentioning
confidence: 71%
“…Myelolipomas are composed of mature fat with a variable proportion of hematopoietic elements [3], Hemorrhage and calcification may also be present [1], They are usually small in size, although tumors 30 cm in size have been reported [5,6], The myeloli poma is thought to arise in the zona fasciculata of the adrenal cortex [1]. Several authors reported an associa tion between myelolipoma, hypertension and obesity [4,7] but Dieckman et al [2] suggested that this association is probably casual. Adrenal function tests were normal [1], The clinical course is usually silent, although some patients, specially those with the largest tumors, may complain of abdominal or flank pain due to hemorrhage, necrosis or mechanical compression of surrounding structures [1,6].…”
Section: Discussionmentioning
confidence: 99%